Transesterifikasi Minyak Limbah Ikan Patin Menggunakan Isopropanol Dengan Variasi Kecepatan Pengadukan Dan Perbandingan Molar Reaktan - Fernando S Sihotang; Nirwana Nirwana; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Transesterification is a reaction between oil (tryglecerida) and alcohol, creating fatty acid alkyl ester and glycerol as it’s by products. Plastisizer is one of the commercial product of fatty acid alkyl ester. Plastisizer is an organic solvent with high boiling point. As a solid, its melting point is considerably low. Plasticizers from bio-oil production is still very limited, it is necessary to develop a bio-oil-based plasticizers. One of vegetable oils that can be used to produce plastisizer, and still has not been utilized optimally is waste cat fish oil. Plastisizer can be synthesized by transesterification using acid catalysts. Most of the transesterification reaction using homogeneous acid catalysts such as H2SO4, HNO3 and HCl are difficult to separate from product. Alternative catalysts that can be used for the transesterification reaction is natural zeolite catalyst which is easily separated from the heterogeneous reaction products. In this research, the synthesis of plasticizers by transesterification reaction used an activated natural zeolite catalysts to H-zeolite, with variations of stirring speed (150, 175 and 200 rpm) and the molar ratio of reactants (1:6, 1:9, and 1:12) , with a fixed variable was 60-65 0C reaction temperature, 6 hours reaction time, and 20% H-zeolite catalyst composition based by weight of waste catfish oil. The test results showed that the molar ratio and stirring speed affects the speed of the reaction to reach equilibrium reaction. The best operating conditions obtained by this research was the molar ratio of 1: 9, stirring speed 150 rpm, 20% catalyst composition and 6 hours reaction time, obtain conversion of 50,7% Product. Characteristics of plasticizers, which produced by this research meets the standards of commercial plasticizers, with 8,96 – 12,41 mPa s viscosity value (400C), 0,882 – 0,894 Specific Gravity (400C) and saponification number is 135, 41 – 161,75 mg KOH, Where, the standards which used by this research are 8,96 – 12,41 mPa s viscosity value (400C), 0,882 – 0,894 Specific Gravity (400C) and saponification number is 133 – 172 mg KOH.